Appropriateness of antibiotic prescriptions during hospitalization and ambulatory care: a multicentre prevalence survey in Korea. (June 2022) - Park, Se Yoon; Moon, Song Mi; Kim, Bongyoung; Lee, Myung Jin; Park, Ji Young; Hwang, Soyoon; Yu, Shi Nae; Lee, Yu-Mi; Lee, Ho Jin; Hong, Kyung-Wook; Park, Kyung-Hwa; Kwak, Yee Gyung; et al.
Highlights: The prevalence of antibiotic prescription was 14.1% on the study date. A significant proportion (27.7%) of antibiotic prescriptions were inappropriate. The commonest indication for therapeutic antibiotics was respiratory tract infections. The most frequently prescribed antibiotics were cephalosporins. Interventions for high-frequency infections and prescription antibiotics are needed. ABSTRACT: Objectives: Antimicrobial resistance is one of the most urgent global health threats. The need for the qualitative evaluation of antibiotic use at the national level is increasing. To identify areas for improvement, we aimed to assess the prevalence and appropriateness of antibiotic prescriptions during hospitalization and ambulatory care in Korea. Methods: The prevalence and appropriateness of antibiotic prescriptions on 29 August 2018 were assessed for 20 hospitals in Korea. Infectious disease specialists determined appropriateness. Except for antiviral and anti-tuberculosis agents, all antibacterial or antifungal agent prescriptions during hospitalization or ambulatory care were evaluated. Results: The prevalence of antibiotic prescription was 14.1% (8, 400/59 216 patients) on the study date. Antibiotics were prescribed for 50.8% of inpatients (6557/12 902), with two or more antibiotics prescribed for 27.4% (1798/6557) of patients. A total of 10 948 prescriptions (7999 therapeutic, 2105 surgical prophylaxes, and 844 medical prophylaxes) were included in the final analysis, and 27.7% of these were inappropriate. Surgical prophylaxis was inadequately prescribed most frequently (54.4%), followed by medical prophylaxis (29.5%) and therapeutic antibiotics (20.5%). The most common indications for therapeutic antibiotics were respiratory (29.1%, n=2332), gastrointestinal (22.4%, n=1791), and urinary tract infections (13.1%, n=1050). The most frequently prescribed antibiotics were cephalosporins (52.0%, n=5490), followed by beta lactam/beta lactamase inhibitors (13.7%, n=1373), fluoroquinolones (9.1%, n=957), and metronidazole (6.6%, n=699). Conclusion: This was the first nationwide qualitative antibiotic prescription adequacy evaluation in Korea. A significant proportion of antibiotic prescriptions were inappropriate. Therefore, interventions for high-frequency infections and prescription antibiotics are needed.